Surgical Considerations for Tumor Tissue Procurement to Obtain Tumor-Infiltrating Lymphocytes for Adoptive Cell Therapy. Issue 4 (July 2022) - Mullinax, John E.; Egger, Michael E.; McCarter, Martin; Monk, Bradley J.; Toloza, Eric M.; Brousseau, Susan; Jagasia, Madan; Sarnaik, Amod
Abstract: Adoptive cell therapy with tumor-infiltrating lymphocytes (TILs), an investigational cellular therapy, has demonstrated antitumor efficacy in patients with advanced solid tumors, including melanoma. Tumor-infiltrating lymphocyte cell therapy involves surgical resection of a patient's tumor, ex vivo TIL expansion under conditions that overcome immunosuppressive responses elicited by the tumor and the tumor microenvironment, administration of a lymphodepleting regimen, and infusion of the final TIL cell therapy product back into the patient followed by interleukin 2 administration to support T-cell activity. The surgeon plays a central role in patient identification and tumor selection—steps that are critical for successful outcomes of TIL cell therapy. Commercialization of TIL cell therapy and its broader access to patients will require education and collaboration among surgeons, oncologists, and cellular therapists. This review highlights the unique role that surgeons will play in the implementation of TIL cell therapy and serves as a contemporary report of best practices for patient selection and tumor resection methods.